The person with hemato-oncological disease: which model of nursing care - Sá, Eunice (2015)
The person with haemato-oncology disease has to deal with all the particulars required by disease and treatment in the different dimensions of their lives. The Haemato-oncology group from Portuguese Oncology Nursing Association, sensitive to this issue, proposed itself to develop a multinational study that would allow to describe the perceptions of nurses working in the haemato-oncology area (inpatient, day hospital and transplants) regarding individualized nursing care: to compare the perceptions of nurses performing functions in different units of haemato-oncology, on individualized nursing care and know the environment factors of the professional practice of these nurses. A study was implemented in 2012, with a descriptive/comparison design, with the nurses working in the Hemato-oncology area (inpatient, day hospital and transplants) in Portugal and fulfilling all the ethical requirements. It was obtained 165 responses from nurses of five different hospitals. We found that nurses direct their care for the individuality of sick people and are aware of this perception. Between health institutions, despite some differences, the lowest values were in Personal Life Situation subscale, followed by the Autonomy/Control on the Decision of the Care and the highest score were in Patient Clinic Situation.Overall we found lower values in the evaluation of professional practice environment. The Work Team and Conflict Management subscales had the lowest scores and Internal Motivation and Leadership and Professional Autonomy in Clinical Practice the highest, with differences between the different contexts on the individual nursing care with haemato-oncology disease.